Integrated pharmacognostic and DNA barcode characterization of Pleiospermium littorale, an IUCN Endangered species from Vietnam - THUY THI PHUONG NGUYEN; DUNG PHUONG NGUYEN; TRIET THANH NGUYEN; TUOI THI HONG DO (Society for Indonesian Biodiversity, 2026)
Abstract. Nguyen TTP, Nguyen DP, Nguyen TT, Do TTH. 2026. Integrated pharmacognostic and DNA barcode characterization of Pleiospermium littorale, an IUCN Endangered species from Vietnam. Biodiversitas 27 (8): d270804. https://doi.org/10.13057/biodiv/d270804. Pleiospermium littorale (synonym Limnocitrus littoralis), Rutaceae) is an IUCN-listed endangered species from Vietnam with limited scientific documentation, particularly regarding its anatomical characteristics and molecular data. This study aimed to provide integrated pharmacognostic and DNA barcode data to support species identification and future quality-control studies. Macromorphological characteristics were documented, while micromorphology, anatomy, epidermal features, stomatal index, and powder microscopy were examined using light microscopy. DNA barcoding was performed using three loci (ITS, matK, and rbcL), and physicochemical parameters were determined using standard pharmacopoeial methods. The species exhibited distinctive pharmacognostic characteristics, including amphistomatic leaves with anomocytic stomata, secretory cavities, abundant prismatic calcium oxalate crystals, sclerenchymatous tissues, and diagnostic powder microscopic features useful for organ identification. The stomatal index was significantly higher on the abaxial leaf surface (10.19±0.70%) than on the adaxial leaf surface (6.29±0.99%). DNA barcoding successfully generated ITS (686 bp), matK (639 bp), and rbcL (528 bp) sequences, providing initial molecular reference data for this endangered species. The combined dataset also facilitates comparison with related Rutaceae taxa and strengthens the taxonomic basis for conservation, authentication, and future pharmacognostic evaluation. These findings present the first integrated morpho-anatomical, pharmacognostic, and multi-locus DNA barcode dataset for P. littorale, providing preliminary baseline data to support its accurate identification and quality standard development.